"Soul", il simpatico "Grande prima" della nostra vita - Fares, Diego (La civiltà cattolica, 2021)
Directed by Pete Docter and Kemp Powers, Soul is an animated film produced by Pixar Animation Studios, which today belongs to Walt Disney Pictures. In our opinion, the most powerful and original metaphor of Soul is that of the “Great Before”, which is the dimension in which souls shape their personalities by participating in the “I-Seminar” before descending to earth. The “Jerry-Counselors”, who define themselves as “the conjunction of all the quantized fields of the universe” and graciously direct everything that happens in the universe, organize the Seminar. Unborn souls are guided by the “mentors”, souls of real people who try to help each person discover his or her “spark” of life.